1998
DOI: 10.1515/znc-1998-11-1211
|View full text |Cite
|
Sign up to set email alerts
|

Chloroacetamide Mode of Action, II: Inhibition of Very Long Chain Fatty Acid Synthesis in Higher Plants

Abstract: H erbicide, C hloroacetam ide, V L C FA , C ucum is sativus, H ordeum vulgare, Zea m ays In short-term -ex p erim en ts [14C ]-labelled m alonic acid, stearic acid and acetate have been incorporated into leaf fatty acids of seedlings of C ucum is sativus, H ordeum vulgare and Zea mays. The p attern of labelled fatty acids changed m arkedly by tre a tm e n t with the chloroacet am ide herbicides m etazachlor, m etolachlor or butachlor. D uring a 2-h incubation time, 1 [!M chloroacetam ide specifically in hibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…Although the approximate I50 value for oleic acid elongation in Scenedesmus for com pounds 4, 5 and 6 were about 10_ 6m , the I50 value Table II Matthes et al (1998). * 2 for the assay with Scenedesmus cells see Couderchet et al (1998).…”
Section: Structure-activity Considerationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the approximate I50 value for oleic acid elongation in Scenedesmus for com pounds 4, 5 and 6 were about 10_ 6m , the I50 value Table II Matthes et al (1998). * 2 for the assay with Scenedesmus cells see Couderchet et al (1998).…”
Section: Structure-activity Considerationsmentioning
confidence: 97%
“…Its phytotoxic symptoms, namely impaired seedling emergence and stunting have been reported as very similar to those of chloroacetamide herbicides, such as alachlor or butachlor (Fukazawa et al, 1995). Re cently, a strong inhibition of very-long-chain fatty acid (VLCFA) biosynthesis by cafenstrole has been found in unicellular Scenedesmus cells (Couderchet et al, 1998), in cucumber cotyledons (Matthes et al, 1998), and with a cell-free micro somal preparation from leek seedlings (Allium porrum-, Böger et al, 2000). Incorporation of exog enously applied [14C]-oleic acid into an insoluble non-lipid fraction of Scenedesmus acutus cells was drastically decreased by the herbicide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fentrazamide inhibited the biosynthesis of very long chain fatty acids as well as chloroacetamides, oxyacetamides, including mefenacet, cafenstrole and thenylchlor. [4][5][6][7][8] Fedtke and Hess et al reported that the morphological effect of mefenacet on green algal cells was similar to that observed for thiocarbamates and chloroacetamides. 9) The macroscopic symptoms of mefenacet on E. oryzicola were dark green coloration, stunting of leaves, and strong growth inhibition of plants.…”
Section: Introductionmentioning
confidence: 83%
“…Cycloheximide (an inhibitor of protein biosynthesis) at 10 mM showed a marked inhibitory effect on the incorporation of 24. 7) Recently, complete inhibition of VLCFA elongases from Arabidopsis thaliana by 100 mM fentrazamide treatment was reported. 8) Although fentrazamide has been used in paddy fields in Japan since its introduction in the late 1990s, the mode of action at the molecular level has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%